The Right To Same-Sex Marriage In The Light Of The Inter-American And European Human Rights Systems, And The Displacement Of The Doctrine Of National Discretion In Mexico - Rogelio López-Sánchez Universidad Autónoma de Nuevo León , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article examines the scope and limits that the figure of same-sex marriage has had within the framework of the inter-American and European human rights systems in relation to the national discretion of its Member States, and how the Supreme Court of Justice of the Mexican Nation (SCJN) has adopted a doctrine of full recognition of that civil institution as a human right and displacing that margin to the detriment of the democratic principle. The Mexican Court has perhaps been the only court in the world to compel all States of the Federation to recognize through jurisprudence the institution of marriage equally (equal marriage) which has had a number of theoretical consequences that were difficult to overcome, as well as a distortion of the democratic principle in Mexico.